EFFECT OF FOLIAR APPLICATION WITH BRASSINOLIDE AND ALGAE EXTRACT (TECAMINE) IN VEGETATIVE AND YIELD CHARACTERISTICS OF APPLE TREE (CV. ANNA) - & Al-esawi, Al-Jumaily (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was conducted in the Apple orchard belong to Department of Horticulture / Collage of Agriculture / University of Baghdad- Abu Ghraib during 2015, in order to investigate the response of four years old Apple trees (CV.Anna) budded on seeding root stock to foliar application with Brassinolide at four levels (0,2,4and 8)mg.g-1 and Algae extract (Tecamin) at four levels (0,2,4,6) ml.L-1 and their interaction between them in some vegetative and yield characters. Each treatment replicated three times with a factorial experiment using RCBD. The number of trees used was 27 trees. The results showed that treatment B3 was significantly increased in total chlorophyll content in leaves, shoot diameter, shoots length and shoot content of C:N Ratio.The treatment T3 gave a high value of shoot diameter and fruit size. While the interaction between the two factors (Brassinolide and Algae extract) B3T3 gave a high value of chlorophyll content in leaves, fruit weight mean, fruit diameter and fruit size (46.10 mg.g-1, 0.2733cm, 93.88gm, 5.387cm and 96.33cm3) respectively, while the interaction B3T1 gave a high a verge of fruit length was reached (5.587cm (while the treatment B3T2 gave a high content of Carbohydrates/Nitrogen Ratio reached to 10.52%.